The Caucasian archaeology of the Holy Land : Armenian, Georgian and Albanian communities between the fourth and eleventh centuries CE - Tchekhanovets, Yana. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2018)
The Caucasian Archaeology of the Holy Land investigates the complete corpus of available literary, epigraphic and archaeological evidence of the Armenian, Georgian and Caucasian Albanian Christian communities' activity in the Holy Land during the Byzantine and the Early Islamic periods. This book presents the first integrated approach to a wide variety of literary sources and archaeological evidence, previously unpublished or revised. The study explores the place of each of these Caucasian communities in ancient Palestine through a synthesis of literary and material evidence and seeks to understand the interrelations between them and the influence they had on the national churches of the Caucasus.